The Implementation of Quality Function Deployment (QFD) Method to Improve Pasteurized Milk Product Quality - Dewi, Shanty Kusuma; Putri, Ananda Rizky Calfintry; Rahmawatie, Layyinatur (Department of Agro-industrial Technology, University of Brawijaya, 2020)
Abstract Pasteurized milk products in Malang Regency hold a significant opportunity to be developed. The number of existing dairy farmers is a supporting factor for the producers in obtaining raw milk supplies. The X milk cooperative unit is one of the producers of pasteurized milk in Malang Regency, in addition to other dairy business competitors. The intense competition forces the X milk cooperative unit to maintain and improve the quality of its milk product to satisfy consumers' demands. The objectives of this research are to determine consumers' demand and formulate corrective actions to improve consumers' satisfaction. QFD is a method of structured product planning and development to ensure that customers' needs and demands can be accommodated in a product. The results of data processing suggest that some quality attributes of milk products that need to be improved based on their degree of importance were milk composition consistency and halal assurance from “Majelis Ulama Indonesia” (MUI) an Indonesian Ulema Council. The right composition of milk keeps the milk taste preferred by the customers consistent, the smell less fishy and the shelf life constant. The second rank attribute was registering to MUI certification, as this certification will increase the product's competitiveness.Keywords: cow milk, house of quality, quality function deployment